The Role of Physical, Social, and Financial Infrastructure on Economic Growth in Indonesia - Adhari, Anggara Wahyu; Khoirunurrofik, Khoirunurrofik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this research is to determine the effects of physical, social, and financial infrastructure on economic growth in Indonesia during 2016-2020 using data from 34 provinces. The infrastructure index is compiled using the Principal Component Analysis (PCA) technique to represent infrastructure indicators. Estimation in this study was carried out using the Panel Corrected Standard Error (PCSE) to improve the Fixed Effect Model which contains problems of multicollinearity, heteroscedasticity, and autocorrelation. The results of this study show that physical infrastructure, social infrastructure, and financial infrastructure have a significant impact on economic growth in Indonesia. Physical and social infrastructure has a positive impact, while financial infrastructure has a negative impact.